Interactive display (B) - Chong, Elton Wei Da (Nanyang Technological University, 2022)
Boards games started out with using pieces to move around demarcated spots on the board and often games are played on tabletops. These games allow for human interactions between players and boards. Emerged from the past couple of decades are Artificial Intelligence (AI) integrated into such board games, AI has been trained and is capable of predicting the player’s next moves by matching current moves to their database. Usually, such games are played by using a mouse and keyboard which get mundane easily after it fails to excite players. Soon after there are companies created video games with motion sensors and hand gesture recognition for input over traditional game controllers using buttons. This has effectively opened up a new market providing players the opportunity to exercise and get fit while playing games in the comfort of their own homes. Such games also allow for multiplayer modes providing players an opportunity to play with their friends or family and maybe even someone online. Thus, this project aims to give a new life to the board game Connect 4 by providing a touchless interactive display for users that uses hand gesture recognition to control where the chips are dropped while maintaining the fundamental of a board game as well as the inclusion of AI player for single-player mode.